Zebrafish (Danio rerio) as a Model System for Diseases in Biological Studies - Sengupta, Manjima; Sengupta, Sudeshna; Khatun, Rojina; Bhattacharya, Malavika (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Background: Zebrafish (Danio rerio) are now a prime model organism in biomedical research due to their genetic similarity to humans, optical transparency in early development stages, and ability to be genetically manipulated with ease. With the prohibition of animal dissection after 2014, and the stringent ethical requirements for the use of rodents such as mice and rats, zebrafish offer a convenient alternative model for disease studies. Their small size, rapid embryonic development, and capacity for recapitulating human disease phenotypes make them particularly suited for the study of multifaceted diseases, like cancer, neurodegenerative diseases, and cardiovascular disease as compared to other model organisms. Aims: The following review aims to investigate the growing value of zebrafish as a model organism in disease research and highlight improvements in cell imaging technologies that further enhance their merit. It also highlights their potential to replace traditional mammalian models in future biomedical research because of ethical, logistical, and experimental advantages. Materials and Methods: The findings of previous scientific research studies and research articles that employed zebrafish as a model system in disease-related research have been gathered and summarized. A literature review was conducted to denote the way that zebrafish have been employed together with advanced imaging techniques to explore a variety of human diseases. Results: Evolution of cell imaging technology has made high-resolution visualization of complex cell and molecular functions possible in zebrafish. It has been demonstrated through research that zebrafish model well most forms of human disorders, and one can achieve experiment outcomes within a short time frame as they grow rapidly. In addition, use of zebrafish circumvents some of the ethical challenges posed by traditional rodent models. Conclusion: The combination of zebrafish as a model organism and high-class cell imaging technologies presents an unprecedented platform for therapeutic design, drug discovery, and disease modelling. With their many advantages and fewer ethical constraints, the zebrafish are poised to become a major model system in future biomedical and translational research.